Rethinking the Role of Microfinance, Agricultural Engagement and Youth Policies in Tackling Unemployment, Livelihood, Empowerment, and Poverty Alleviation in Tanzania - Joseph Magali (Journal of Sustainable Economics, 2026)
Youth unemployment is a challenge for many developing countries, including Tanzania. The article discusses the status of youth employment in Tanzania and articulates the causes and strategies to address it. The article examines how microfinance, agricultural engagement, and youth policies address youth unemployment by improving livelihoods, empowering youth, and alleviating poverty. The study used 81 articles retrieved from Scopus (16) and Google Scholar (65). The findings revealed that strategies to address youth unemployment in Tanzania, such as entrepreneurship training programmes, youth policies, and the establishment of youth employment projects, including agricultural activities, have not been sufficient to overcome these challenges. The findings further indicate that scholars have documented microfinance's contributions to youth employment, poverty alleviation, and livelihood improvement. The findings reveal that microfinance has contributed positively to overcoming youth unemployment. However, the findings indicate that the challenge of loan repayment is a barrier to the sustainability of microfinance. The study recommends that policymakers implement policies that promote youth employment by linking income-generating activities to microfinance services and enforcing loan repayment among youth in Tanzania.